ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA TIPE HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI POLA BILANGAN DI KELAS VIII MTs NEGERI 1 PALU: Analysis of Students’ Ability to Solve Higher Order Thinking Skills (HOTS) Mathematics Problems on Number Pattern in Grade VIII of MTs Negeri 1 Palu - Astuti, Mega; Karniman, Tegoeh S. (Universitas Tadulako, 2024)
The purpose of this study was to analyze the ability of students to solve Higher Order Thinking Skill (HOTS) type questions on number pattern material in Class VIII MTs Negeri 1 Palu. The type of research used is descriptive qualitative research. The subjects in this study were three students of class VIII MTs Negeri 1 Palu in the odd semester of the 2023/2024 school year consisting of one student each with high, medium, and low abilities. Data collection techniques used written tests and interviews. The results of this study indicate that (1) high ability students are able to solve well on HOTS problems on the subject of number patterns on indicators C4 and C5 by fulfilling all stages of problem solving, (2) medium ability students are only able to solve HOTS problems on the subject of number patterns on indicator C4, but on indicator C5 have not been able to solve well. (3) low ability students were not able to solve HOTS problems on the subject of number patterns on indicator C4 and also on indicator C5 were not able to solve well.